Occurrence and chemical composition of minerals from the Pallancata Ag mine, Peru - Yoo, Bong Chul (2019)
Pallancata Ag mine is located at the Ayacucho region 520 km southeast of Lima. The geology of mine area consists of mainly Cenozoic volcanic-intrusive rocks, which are composed of tuff, andesitic lava, andesitic tuff, pyroclastic flow, volcano clasts, rhyolite and quartz monzonite. This mine have about 100 quartz veins in tuff filling regional faults orienting NW, NE and EW directions. The Ag grades in quartz veins are from 40 to 1,000 g/t. Quartz veins vary from 0.1 m to 25 m in thickness and extend to about 3,000 m in strike length. Quartz veins show following textures including zonation, cavity, massive, breccia, crustiform, colloform and comb textures. Wallrock alteration features including silicification, sericitization, pyritization, chloritization and argillitization are obvious. The quartz veins contain calcite, chalcedony, adularia, fluorite, rutile, zircon, apatite, Fe oxide, REE mineral, Cr oxide, Al-Si-O mineral, pyrite, sphalerite, chalcopyrite, galena, electrum, proustite-pyrargyrite, pearceite-polybasite and acanthite. The temperature and sulfur fugacity (fs2) of the Ag mineralization estimated from the mineral assemblages and mineral compositions are ranging from 118 to 222 °C and from 10-20.8 to 10-13.2 atm, respectively. The relatively low temperature and sulfur-oxygen fugacities in the hydrothermal fluids during the Ag mineralization in Pallancata might be due to cooling and/or boiling of Ag-bearing fluids by mixing of meteoric water in the relatively shallow hydrothermal environment. The hydrothermal condition may be corresponding to an intermediate sulfidation epithermal mineralization.